Laser speckle size and contrast investigation of volumetric scattering from controlled turbid phantoms and mouse skin tissues - Carla Kulcsar; Daniel C. Louie; Alex Vitkin (iScience)
Summary: The potential of spatial laser speckle analysis to interrogate scattering properties of volumetric optical tissue-like phantoms and biological tissues is examined. The simple and inexpensive experimental setup consists of a HeNe laser illuminating turbid samples to acquire speckle patterns in backscattering geometry. Theoretical Monte Carlo simulations of subsurface light fluence patterns and scattering statistics are used to interpret the experimental findings, in an effort to help expand established speckle theory from rough surface effects to volumetric scattering processes. Beyond controlled phantom studies, initial results from normal and pathologic biological tissues are also presented and discussed. Building on previous research that attempts to link specific stochastic speckle metrics to medium scattering properties, this study suggests that a combination of speckle contrast and speckle size can be related to varying scattering coefficients, toward distinguishing samples by their underlying scatterer size and concentration.